Factors Determining the Regional Industrial Development and Industrial Production Potential: The Case of Samarkand Region - Jasur Juraboevich Yakhshilikov (Universitas Muhammadiyah Sidoarjo, 2020)
This article discusses the industry sector as the main factor affecting the development of our economy. It is well known that the development of industries contributes to the development of other sectors of the economy. Factors affecting the potential of industrial production were studied and analyzed using some boundary values that represent the sustainable development of the industry in the Samarkand region. Investments play an important role in the sustainable development of industry in the region. The analysis of the linear correlation between investments in fixed assets and GDP, as well as the following empirical models between gross industrial output and its factors for the Republic of Uzbekistan and the Samarkand region are presented. Conclusions are based on models.